Modes of relating to contingency: An exploration of experiences in advanced cancer patients. Issue 4 (20th December 2016) - Kruizinga, Renske; Hartog, Iris D.; Scherer-Rath, Michael; Schilderman, Hans; Van Laarhoven, Hanneke
ABSTRACT: Objective: Throughout their lives, people are confronted with unexpected life events, which can be difficult to incorporate into their life narratives. Such a confrontation can result in an experience of contingency. Different ways of relating to contingency have been described by Wuchterl: denying, acknowledging, and "encounter with the Other." In the present article, we aim to trace these theoretical distinctions in real-life experiences of patients. Method: We analyzed 45 interviews using the constant comparative method with a directed content analysis approach in the Atlas.ti coding program. The interviews originated from a randomized controlled trial evaluating an assisted reflection on life events and ultimate life goals. Seven spiritual counselors from six hospitals in the Netherlands conducted the interviews from July of 2014 to March of 2016. All 45 patients had advanced cancer. Results: We found four different modes into which relating to contingency can be classified: denying, acknowledging, accepting, and receiving. With denying, patients did not mention any impact of the life event on their lives. In acknowledging, the impact was recognized and a start was made to incorporate the event into their life. In accepting, patients went through a process of reinterpretation of the event. In receiving, patients talked about receiving insights from their illness and living a more conscious life. Significance of results: Our study is the first to investigate the different ways of relating to contingency in clinical practice. The defined modes will improve our understanding of the various ways in which cancer patients relate to their disease, allowing caregivers to better target and shape individual care.